Product Innovation And Marketing Assistance To Eco Greeen Handcraft MSMEs - Latifah Anom; Eka Adiputra; Murtini Murtini; Abdul Azis Safii; Hasan Bisri (TGO Journal of Community Development, 2023)
The condition of the export market, which is very sluggish, has put the MSME economy and the people who produce environmentally friendly handcrafts in Kasiman Village in an alarming condition; exports of handcraft products have stopped entirely as a result of the crisis after the Covid 19 Pandemic and the war that occurred in Europe. This mentoring program aims to help provide solutions for target partners. Handcraft product innovation and digital-based marketing assistance are expected to boost sales of handcraft products to compete in the local market by targeting millennial generation consumers and e-commerce and social media-based sales strategies. The implementation of innovation assistance for the diversification of handcraft products and the implementation of digital marketing has been going well, which has proven to have succeeded in boosting the sales of handcraft products for the people of Kasiman Village through various e-commerce channels, social media, or direct sales at galleries selling home decor and handcraft products made from friendly materials-environment in Kasiman Village.